Spectroscopic and structural properties of CeO2 nanocrystals doped with La3+, Nd3+ and modified on their surface with Ag nanoparticles. Issue 5 (May 2021) - Michalska, Monika; Lemański, Karol; Sikora, Andrzej
Abstract: The purpose of this work is to present our efforts focused on applications of chemical synthesis of nanocrystalline cerium dioxide (CeO2 ) powders doped with La 3+ ions and CeO2 :Nd 3+ modified, on their surface, with Ag nanoparticles (NPs). The synthesized powders were examined by X-ray powder diffraction (XRD), absorption, emission spectroscopy, scanning electron (SEM) and atomic force microscopy (AFM). The relations between crystallographic properties and stability of CeO2 compounds doped by La ions and surface-modified by Ag were studied. XRD patterns revealed that all studied samples are single-phase and crystallized in the cubic fluorite-type structure, in space group Fm-3m. The average crystallite sizes estimated by Rietveld method of series: La-doped CeO2 were in the range of 7–14 nm, and CeO2 :1%Nd 3+ /n-Ag (n: 1- 5wt.%) were found to be in the range of 29–34 nm, respectively. The lattice parameter a for La-doped CeO2 powders varying from 5.416 to 5.482 Å with increasing content of La 3+ ions from 0 to 20wt.%, respectively. For series of CeO2 :Nd 3+ /n-Ag materials lattice parameter a was at the same level and in accordance with the standard value a0 = 5.411 Å (ICDD - 43-1002). The SEM and AFM observations depicted the grainy structure of all obtained CeO2 -powder samples. The estimated grain size ranged from 50 to 500 nm. The diverse grain shapes and packing was remarked in the samples. According to our knowledge, the relationship between the structural, spectroscopic and morphological characteristics of CeO2 samples was presented in this work for the first time. Abstract : Cerium dioxide, CeO2, Silver nanoparticles, Lanthanides, Spectroscopy.